Highly sensitive ethanol sensor based on TiO2 nanoparticles and its photocatalyst activity - Singh, Preeti; MAbdullah, M.; Sagadevan, Suresh; Kaur, Chanmeet; Ikram, Saiqa (Elsevier, 2019)
Photo-catalytic decolorization or adsorption of an aqueous solution of 3 ppm of brilliant cresyl blue (BCB) in a suspension of 0.26 gm/100 ml of TiO 2 metal oxide semiconductor as a catalyst, was achieved by using 200Watts UV lamp from an external source. The disappearance of the original colored dye concentration with irradiation time was monitored using UV-VIS Spectrophotometer. It was found that 74% of BCB dye was degraded after 120 min of irradiation time. In addition, the sensing properties of the TiO 2 films were examined on behalf of numerous concentrations of ethanol in the liquid phase by a straightforward and dependable I–V procedure at normal room conditions. The sensitivity of the sensor was found to be ˜0.052 mAM −1 cm -2 for ethanol. Thus, the degradation rate and the subsequent chemical sensing properties of TiO 2 nanoarchitecture are of immense importance for the functions of TiO 2 structure as a photo-catalyst and chemical sensor. © 2019 Elsevier GmbH